Developing Vaccines for SARS-CoV-2 and Future Epidemics and Pandemics: Applying Lessons from Past Outbreaks - Billington, John (Health Secur, 2020)
The COVID-19 pandemic is a stark reminder of the heavy toll that emerging infectious diseases (EIDs) with epidemic and pandemic potential can inflict. Vaccine development, scale-up, and commercialization is a long, expensive, and risky enterprise that requires substantial upfront planning and offers no guarantee of success. EIDs are a particularly challenging target for global health preparedness, including for vaccine development. Insufficient attention has been given to challenges, lessons learned, and potential solutions to support and sustain vaccine industry engagement in vaccine development for EIDs. Drawing from lessons from the most recent Ebola epidemic in the Democratic Republic of the Congo, as well as the 2009 H1N1 influenza, 2014-2016 Ebola, and 2015-16 Zika outbreaks preceding it, we offer our perspective on challenges facing EID vaccine development and recommend additional solutions to prioritize in the near term. The 6 recommendations focus on reducing vaccine development timelines and increasing business certainty to reduce risks for companies. The global health security community has an opportunity to build on the current momentum to design a sustainable model for EID vaccines.